PRAKTIK SEWA LAHAN PERTANIAN DITINJAU DARI HUKUM POSITIF DAN HUKUM ISLAM: Studi Kasus di Blok Balir Mekarjaya Gantar Indramayu - Buwono; Irvan Iswandi (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
This undergraduate thesis examined the practice of leasing agricultural land in terms of positive law and Islamic law in Balir Block, Mekarjaya, Gantar, Indramayu. The subject matter of this research is the implementation of agricultural land leases in Balir Block, Mekarjaya Village, Gantar District, Indramayu Regency, and its review in terms of positive law and Islamic law. The purpose of this study is to find out and understand how the implementation of agricultural land leasing in Balir Block, Mekarjaya Village, Gantar District, Indramayu Regency. In addition, it is to find out and understand the review of agricultural land leasing practices in Balir Block in terms of positive law and Islamic law. The research method in this study uses a qualitative method whose data collection is carried out through observation, interviews, and documentation of the parties to the agricultural land lease contract in Balir Block, Mekarjaya Village, Gantar District, Indramayu Regency. Based on research conducted in Balir Block regarding the practice of leasing land, it can be concluded that there is an agreement between the owner and the tenant of the land at a certain price and time without an agreement letter. In terms of positive law with article 1548 of KUHPer, the lease that occurs in Balir Block is not in accordance with positive law because there is no written agreement between the tenant and the landowner. Thus, if there is a default in the future, it will be difficult to prove a violation of the land lease agreement. Meanwhile, according to Islamic law, if it is viewed in terms of the terms and conditions of leasing, everything has been fulfilled, but in terms of the benefits of the goods, it cannot be assessed because of the uncertainty about the profit and loss obtained by the tenant.